API Testing and Development with Postman. - Dave Westerveld; PACKT (GB: Packt, 2024)
Avoid common API coding pitfalls and make test automation effortless with Postman and the Newman CLI Key Features Learn the tenets of effective API testing and design with workflow testing and more Gain an in-depth understanding of Postman's new and existing features, including Mock Servers Know when and how to use Postman to create high-quality APIs for software and web apps Book Description Postman is an invaluable tool for exploration and testing of web APIs and helping testers and developers figure out how an API works. With Postman, you can create effective test automation for any APIs, and this guide will help you unleash its full potential. API Testing and Development with Postman is an invaluable resource for anyone who wants to create a good quality API, but isn't sure how to go about it. This guide will help you unleash the full potential of Postman's test automation capabilities. A combination of theory coupled with real-world examples will help you learn how to use Postman to create well-designed, documented, and tested APIs. After you've familiarized yourself with the theory, you'll move on to hands-on projects that will teach you how to add test automation to an existing API. You'll also learn some of the new and powerful features that Postman has that can help you avoid introducing bugs. This second, fully updated edition features new chapters on workflow testing, creating and using mock servers, API security testing, and performance testing. The new and expanded information in this edition will help you future-proof your APIs. By the end of this book, you'll be able to use Postman to set up and run API tests for any API that you are working with. What you will learn Find out what is involved in effective API testing Leverage Postman to improve the quality of you API Use data-driven testing in Postman to create scalable API tests How to create and use a Mock Server in Postman Verify and improve the quality of an API using contract testing Understand the basic principles of security testing Get to grips with functional and non-functional testing of an API Discover how to use industry standards such as OpenAPI and mocking Who this book is for The book is for software testing professionals and software developers looking to improve product and API quality through API test automation. You'll also find this book useful if you have a basic understanding of APIs and want to build your skills for creating, testing, and documenting them. The book assumes beginner-level knowledge of JavaScript and API development.
Data in extended ASCII character set.
Mode of access: Internet.